2011
DOI: 10.1007/s10549-011-1618-8
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of metachronous contralateral breast cancer: importance of stage, age and interval time between the two diagnoses

Abstract: Studies comparing the prognosis after contralateral breast cancer (CBC) with that after unilateral breast cancer (UBC) shows conflicting results. We assessed the risk of breast cancer-specific death for women with metachronous CBC compared to those with a UBC in 8,478 women with invasive primary breast cancer registered in the Guy's and St. Thomas' Breast Cancer Tissue and Data Bank. Risk factors associated with breast cancer-specific death for women with CBC were estimated using Cox proportional hazards model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
35
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
3
35
1
1
Order By: Relevance
“…2008; Verkooijen et al 2007;Vichapat et al 2011a). In the Canton of Vaud, the age incidence pattern of CBC was examined as it was not comparable to the pattern of incidence for most cancers or breast cancer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…2008; Verkooijen et al 2007;Vichapat et al 2011a). In the Canton of Vaud, the age incidence pattern of CBC was examined as it was not comparable to the pattern of incidence for most cancers or breast cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The WHO Classification of Tumours of the Breast adopts this definition, which is used frequently in studies (Alkner et al 2011;Hartman et al 2007;Sandberg et al 2012b;Schmid et al 2011), but also mentions the benefit of a longer time interval for epidemiological [10] assessments. Many studies favour a longer cut-off time to distinguish bilateral breast cancers (Bernstein et al 2003;Londero et al 2014;Nichols et al 2011;Rubino et al 2010;Schaapveld et al 2008;Verkooijen et al 2007;Vichapat et al 2011a;Vichapat et al 2012;Vichapat et al 2011b;Yerushalmi et al 2009). As there is no consensus concerning these definitions, we conducted further analyses with different cut-off times.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Bilateral breast cancer is known to be associated with a higher risk of mortality than unilateral breast cancer, with poorer outcomes recorded in a subgroup of patients that exhibited younger-onset and shorter durations between the first and second cancer diagnosis. 11,[17][18][19] Several studies have reported mean durations between the occurrence of the primary breast cancer and CBC as being > 5 years, which means patients need to pay careful attention to their contralateral breast for a significant amount of time after receiving treatment for the primary breast cancer. 17,20 In these patients, an annual MMG and physical examination are recommended as routine practice.…”
Section: Discussionmentioning
confidence: 99%
“…Although many studies have shown that CBCs tend to have more favorable tumor characteristics, studies have shown that patients who develop CBCs in a short interval from their primary cancer have worse survival than those who develop a CBC at a longer interval. [43][44][45][46][47] Patients who had worse survival with CBC were young patients, patients with large tumors, and node-positive patients. [44][45][46] It is not clear if the reported worse survival is because these CBCs represent aggressive biology of the primary tumor, distant metastatic disease, or perhaps just older, inferior systemic treatments.…”
mentioning
confidence: 99%
“…[43][44][45][46][47] Patients who had worse survival with CBC were young patients, patients with large tumors, and node-positive patients. [44][45][46] It is not clear if the reported worse survival is because these CBCs represent aggressive biology of the primary tumor, distant metastatic disease, or perhaps just older, inferior systemic treatments. Studies have also examined how CPM affects survival in those patient cohorts who are at higher risk for CBC.…”
mentioning
confidence: 99%